Novel mutations in FH and expansion of the spectrum of phenotypes expressed in families with hereditary leiomyomatosis and renal cell cancer. Issue 1 (3rd June 2005) - Wei, M-H; Toure, O; Glenn, G M; Pithukpakorn, M; Neckers, L; Stolle, C; Choyke, P; Grubb, R; Middelton, L; Turner, M L; Walther, M M; Merino, M J; et al.
Abstract : Background: Hereditary leiomyomatosis and renal cell cancer (HLRCC; OMIM 605839) is the predisposition to develop smooth muscle tumours of the skin and uterus and/or renal cancer and is associated with mutations in the fumarate hydratase gene ( FH ). Here we characterise the clinical and genetic features of 21 new families and present the first report of two African-American families with HLRCC. Methods: Using direct sequencing analysis we identified FH germline mutations in 100% (21/21) of new families with HLRCC. Results: We identified 14 germline FH mutations (10 missense, one insertion, two nonsense, and one splice site) located along the entire length of the coding region. Nine of these were novel, with six missense (L89S, R117G, R190C, A342D, S376P, Q396P), one nonsense (S102X), one insertion (111insA), and one splice site (138+1G>C) mutation. Four unrelated families had the R58X mutation and five unrelated families the R190H mutation. Of families with HLRCC, 62% (13/21) had renal cancer and 76% (16/21) cutaneous leiomyomas. Of women FH mutation carriers from 16 families, 100% (22/22) had uterine fibroids. Our study shows that expression of cutaneous manifestations in HLRCC ranges from absent to mild to severe cutaneous leiomyomas. FH mutations were associated with a spectrum of renal tumours. No genotype-phenotype correlations were identified. Conclusions: In combination with our previous report, we identify 31 different germline FH mutations in 56 families with HLRCC (20 missense, eight frameshifts, two nonsense, and one splice site). Our FH mutation detection rate is 93% (52/56) in families suspected of HLRCC.